GENDER AS A LINGUISTIC CATEGORY: THEORETICAL FOUNDATIONS AND RESEARCH TRENDS - Feruza Akhmedova; Laylo Rahimovna Raupova (Western European Studies, 2026)
This article examines the historical development and theoretical foundations of gender studies within the field of linguistics, highlighting the emergence of a distinct scientific direction commonly referred to as linguistic genderology. The study traces key phases in the evolution of gender research — from early notions of biological determinism to the transitional period and the advent of direct gender studies. It evaluates how gender categories have been conceptualized in language and discusses the influence of seminal scholars such as Jespersen, Moutner, and later sociolinguistic and feminist theorists. The article also analyzes major theoretical approaches, including sociolinguistic gender research, feminist linguistics, psycholinguistic perspectives, masculinity studies, and cross-cultural linguistic investigations. Critiques of early feminist linguistic theories and the integration of gender as a category in contemporary linguistic paradigms are discussed. The study demonstrates that gender has become a central analytical category across diverse linguistic subfields, significantly enriching the understanding of language, society, and identity
Keywords: gender and language; linguistic genderology; biological determinism